Direct evidence for charge stripes in a layered cobalt oxide - Boothroyd, A; Babkevich, P; Freeman, P; Enderle, M; Prabhakaran, D (Nature Publishing Group, 2016)
Recent experiments indicate that static stripe-like charge order is generic to the hole-doped copper oxide superconductors and competes with superconductivity. Here we show that a similar type of charge order is present in La5/3Sr1/3CoO4, an insulating analogue of the copper oxide superconductors containing cobalt in place of copper. The stripe phase we have detected is accompanied by short-range, quasi-one-dimensional, antiferromagnetic order, and provides a natural explanation for the distinctive hourglass shape of the magnetic spectrum previously observed in neutron-scattering measurements of La2−xSrxCoO4 and many hole-doped copper oxide superconductors. The results establish a solid empirical basis for theories of the hourglass spectrum built on short-range, quasi-static, stripe correlations.